Powrót (2003) Andrieja Zwiagincewa jako film inicjacyjny - Karpińska, Zuzanna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2024)
The subject of this paper is Andrey Zvyagintsev’s film The Return (2003). In the Polish film studies literature, both the debut film and other works by this Russian director are analyzed primarily in terms of iconographic references to the Christian religion, which, although meaningful, are not the only important cultural contexts present in The Return, according to this author. The main problem addressed in the text is the way in which the rites of passage function in Zvyagintsev’s work and the meaning of initiation in relation to the figure of the Father and the “religious” plane of interpretation of the film.